Maternal and neonatal outcomes in women with severe pre-eclampsia undergoing cesarean section: a 10-year retrospective study from a single tertiary care center: anesthetic point of view. (16th December 2016) - Chumpathong, Saowapark; Sirithanetbhol, Somkiet; Salakij, Bhurinud; Visalyaputra, Shusee; Parakkamodom, Sudta; Wataganara, Tuangsit
Abstract: Objective : This study is aiming to determine an actual incidence and characteristics of complications in cesarean section for severe pre-eclampsia (PE) by analysis of a large cohort from a single tertiary care center according to two choices of anesthesia. Methods : Electronic medical records of pregnant women complicated with severe PE delivered by cesarean section from January 2002 to December 2011 were retrospectively reviewed. Medical records of their corresponding neonates were also identified and reviewed. Results : A total of 701 women and 740 neonates (28 twin pairs) were identified. Anesthetic techniques were spinal anesthesia (SA) (88%) and general anesthesia (GA) (12%). Total maternal and neonatal deaths were 0.3% and 1.2%, respectively. Patients in GA group had a higher incidence of coagulopathy, immediate postpartum hemorrhage, intensive care unit admission, renal failure, respiratory complications, and death ( p < 0.05). Neonates born from women in GA group had a higher incidence of lower birth weight, birth asphyxia, prematurity, neonatal intensive care admission, respiratory complications, and death ( p < 0.05). Conclusion : Spinal anesthesia can be safely administered to severely pre-eclamptic parturients undergoing cesarean section. General anesthesia is associated with more untoward outcomes, as it has been chosen in patients with more severity of the disease.